The Hexameric Resorcinarene Capsule as a Brønsted Acid Catalyst for the Synthesis of Bis(heteroaryl)methanes in a Nanoconfined Space - Gambaro, Stefania; La Manna, Pellegrino; De Rosa, Margherita; Soriente, Annunziata; Talotta, Carmen; Gaeta, Carmine; Neri, Placido (Frontiers in Chemistry, 2019)
Herein, we show that the hexameric resorcinarene capsule C is able to catalyze the formation of bis(heteroaryl)methanes by reaction between pyrroles or indoles and carbonyl compounds (-ketoesters or aldehydes) in excellent yields and selectivity. Our studies show that the capsule, plays a double catalytic role either as a H-bond catalyst, for the initial activation of the carbonyl substrate, and as a Brønsted acid catalyst, for the dehydration of the intermediate alcohol.